Pengaruh Inovasi, Kreativitas Dan Etika Bisnis Terhadap Bisnis Dalam Novel Gadis Kretek Karya Ratih Kumala - Satria Kamal; Muhammad Fajar Ramadan; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out and prove that innovation, creativity and business ethics are needed for business sustainability in the novel Gadis Kretek by Ratih Kumala. The method used is a qualitative method with a descriptive approach based on the novel Gadis Kretek by Ratih Kumala. The results of this research are about the importance of innovation, creativity and business ethics in business sustainability as well as the importance of making business innovations that can keep up with current developments.